Directional diffusion of moisture in carbon fibre-epoxy composites: experiments and modelling - Feras Korkees (20th International Conference on Composite Materials, Copenhagen, 19-24th July 2015, 2015)
Water diffusion into composites in different directions was examined in this study, with the aim of determining the best way of measuring diffusion coefficients and also to provide values to compare with model predictions. The water absorption behaviour of unreinforced epoxy resins and carbon fibre reinforced epoxy composite materials was examined with long term exposure to different environmental conditions. Initial Fickian absorption was observed followed by a slower second stage that continues for at least 3.7 years. Fibre architecture was found to be an important aspect controlling absorption, where water diffusion along fibres was observed to be about three times faster than across the fibres and about seven times faster than through the thickness. A three-dimensional finite element computer model based on Fickian diffusion behaviour was developed to predict the levels of moisture absorption under hot/humid environments. A multi-scale modelling approach was used which allows the results of simulations at the microstructural level to be used to predict the diffusivities in different directions. Experimental results provided a baseline for the validation of the model, and comparison of these data with model predictions showed close matching and good agreement. The diffusion showed high dependency on the detailed microstructure.